PENINGKATAN PRESTASI BELAJAR MATA KULIAH MEKANIKA TEKNIK I MELALUI QUIS MAHASASISWA JURUSAN PENDIDIKAN TEKNIK BANGUNAN - V LILIK HARIYANTO (Jurnal Kependidikan, 2004)
Abstract This action research aims to: (1) generally to improve learning quality of the Engineering Mechanics I Subject for the Building Engineering Education in the Building Engineering Education Department, Faculty of Engineering, the State University of Yogyakarta, for graduated quality improvement, (2) specifically to observe the learning strategy effectiveness of the Engineering Mechanics I Subject through intensity and effectiveness improvement of quiz form practices. The research is a classroom action research. The observation tools use: (1) lecture attendance sheets, (2) observation sheets, and (3) score sheet to note quiz score. The evaluation was conducted using a form-form test. The data analysis uses descriptive statistics to figure out the data condition of interval and transferred data. The research result indicates that: (1) By conducting lectures accompanied by quiz tests for the Engineering Mechanics Subject, the learning achievement will increase, (2) some test-test treatments indicate  that the score achievement tends to increase, (3) Viewed from motivation and student interrelation aspects, the learning activity which always conduct test-tests indicates a dynamic learning atmosphere and inducing a high learning motivation, (4) the learning activity which always conduct tests-tests impacts the students always being ready to participate (more intense) on the delivered lectures, and (5) the faced handicap is it requires a subject problem-bank. Keywords: engineering mechanics, quiz